Muscle stiffness and rate of torque development during sprint cycling - Watsford, M.; Ditroilo, M.; Fernandez-Pena, E.; D'Amen, G.; Lucertini, F. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Crank torque (CT) application and rate of CT development (RCTD) are important considerations in sprint cycling. The stiffness of the musculotendinous unit is related to the isometric rate of torque development (RTD); however, this relationship has yet to be examined in sprint cycling.